2008
DOI: 10.1017/s0007114507839006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of milk fermented byLactobacillusgasseriSBT2055 on adipocyte size in rats

Abstract: Despite adequate scientific evidence of the potential benefits of probiotics to human health or disease prevention, their contribution to the growth of adipose tissue remains to be established. Four-week-old male Sprague-Dawley rats were fed a diet containing skim milk (control diet) or skim milk fermented by Lactobacillus gasseri SBT2055 (LGSP diet) for 4 weeks. Their body weight gain, adipose tissue weight, adipocyte size distribution profile, blood and hepatic lipids, and serum leptin, glucose and adiponect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(78 citation statements)
references
References 36 publications
4
71
0
3
Order By: Relevance
“…Lee et al in an experimental study found that Lactobacillus rhamnosus produce conjugated linoleic acid and indicate anti-obesity effects in diet-induced obese mice (18). Sato et al evaluated the effects of milk fermented by Lactobacillus gasseri on adipocyte size in rats and achieved similar results (19). Ley RE et al evaluated 16SrRNA gene sequences from the gutmicrobiota of genetically obese ob/ob mice.…”
Section: Discussionmentioning
confidence: 96%
“…Lee et al in an experimental study found that Lactobacillus rhamnosus produce conjugated linoleic acid and indicate anti-obesity effects in diet-induced obese mice (18). Sato et al evaluated the effects of milk fermented by Lactobacillus gasseri on adipocyte size in rats and achieved similar results (19). Ley RE et al evaluated 16SrRNA gene sequences from the gutmicrobiota of genetically obese ob/ob mice.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies [106][107][108][109][110][111][112][113][114][115][116][117][118] have demonstrated the beneficial effects exerted by probiotics containing Lactobacillus strains on animals and human subjects, showed in Table 2 and Table 3, respectively.…”
Section: Probioticsmentioning
confidence: 96%
“…Several studies show that the use of this microorganism in rats decreased visceral fat by enhancing lipid excretion (Yonejima, Ushida, Mori, 2013), reduced adipocyte size (Sato et al, 2008;Hamad et al, 2009), and reduced body weight (Kang Yun, Park, 2010;Kang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%